Neonatal Purpura Fulminans by an Unusual Pathogen: Elizabethkingia meningoseptica - Rakesh Kumawat; Gouda Ankula Prasad Kartikeswar; Tushar Parikh (Wolters Kluwer Medknow Publications, 2022)
Background: Neonatal purpura fulminans (PF) is a rare disorder characterized by the formation of dermal microvascular thrombosis associated with disseminated intravascular coagulation (DIC). It can be caused by inherited protein C or protein S deficiency or severe sepsis with DIC due to organisms such as Streptococcus pneumoniae and Gram-negative bacteria. Clinical Description: A preterm boy of 31-week gestation and weighing 1480 g was delivered by cesarean section. There were no risk factors for sepsis. He presented with respiratory distress after birth, was shifted to the neonatal intensive care unit (NICU), was diagnosed as respiratory distress syndrome, and was managed as per standard protocol. Management: On the 6th day of life, the neonate developed pulmonary hemorrhage, multiple purpura on his upper and lower extremities, and shock. Raised D-dimer (>400 ng/ml), increased prothrombin and activated partial thromboplastin time, and thrombocytopenia (6000/μL) were indicative of DIC. The blood culture isolated Elizabethkingia meningoseptica. Meningitis was ruled out. Supportive care included fresh frozen plasma and platelet transfusion, antibiotics as per drug sensitivity, and granulocyte colony-stimulating factor. The baby improved and the lesions healed with scarring. Protein S and protein C deficiency was excluded on follow-up. On follow-up, at corrected age of 6 months, the baby was developmentally normal. Three additional cases were identified in the unit around the same time, however outbreak investigation could not identify origin of the pathogen. Conclusion: We could not find any earlier publications of neonatal PF due to E. meningoseptica septicemia. This organism is a cause of sepsis and meningitis in preterm babies and outbreaks in NICU settings. Early identification, meticulous assessment, and prompt specific antimicrobial treatment are important for survival.